Use of Traditional Recipes for Oral Care by Local People in Janzour City, Libya: A Qualitative Study - Ayman Elhaji; Omolade Femi-Ajao; Wafa Kashbour (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objectives: Traditional medicine (TM) has gained attention from the public globally in recent times. However, a lack of studies is identified for individuals’ use of traditional medicine to treat dental issues. Libya’s traditional medicine is an example of traditions that include a number of plant- and non-plant-based approaches to dental and oral health. A qualitative descriptive study was used to explore the views on, use of, and access to TM in dentistry as an alternative to conventional dental care and oral pain relief among Libyans. A purposive sample of residents older than eighteen living in the city of Janzour was used, and sixteen semi-structured individual interviews were conducted virtually. The interviews aimed to gather data, including locally used names for plants used medicinally for oral health, ways of using the treatments, their effectiveness, adverse impacts, and how far each remedy was in popular use. Data analysis was conducted, and the results were fairly consistent and indicated relatively high levels of knowledge and usage of TM. Three main themes were extracted from the interviews:1) Different perspectives of the participants on TM. 2) Current practice and experience with TM. 3) Reasons for choosing TM. This study provides understandings for dentistry professionals of the kinds of traditional medicines which the public use for oral health. Building such understandings and awareness of the use of traditional medicines can help dental professionals to promote discussions of the practices which patients use, providing an opportunity for education in this area.